2006
DOI: 10.1007/s11248-006-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of milk from transgenic goats expressing human lysozyme in the mammary gland results in the modulation of intestinal microflora

Abstract: Lysozyme is a key antimicrobial component of human milk that has several health-promoting functions including the development of a healthy intestinal tract. However, levels of lysozyme in the milk of dairy animals are negligible. We have generated transgenic dairy goats that express human lysozyme (HLZ) in their milk in an attempt to deliver the benefits of human milk in a continual fashion. To test the feasibility of this transgenic approach to achieve a biological impact at the level of the intestine, feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 16 publications
3
55
1
2
Order By: Relevance
“…Using standard culturing techniques, total coliform and E. coli counts in the duodenum and ileum of HLZ-fed pigs tended to be lower than in control-fed pigs, similar to results seen when starting with 14-day-old pigs (5,30). These results indicate the reproducibility of the effect of HLZ milk in differently aged animals at this level of detail.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Using standard culturing techniques, total coliform and E. coli counts in the duodenum and ileum of HLZ-fed pigs tended to be lower than in control-fed pigs, similar to results seen when starting with 14-day-old pigs (5,30). These results indicate the reproducibility of the effect of HLZ milk in differently aged animals at this level of detail.…”
Section: Discussionsupporting
confidence: 72%
“…We have developed transgenic dairy goats that express human lysozyme (HLZ) in their milk at 68% the level normally found in human milk (29) with the goal of incorporating the beneficial protective properties of human milk into readily available livestock milk in order to promote the intestinal and overall health of people of all ages. We previously demonstrated that consumption of milk from HLZ-transgenic goats by animal models results in the modulation of Escherichia coli and total coliform levels in the small intestine as determined using standard culture techniques (30), resistance to intestinal colonization by pathogenic E. coli (5), and histological and cytokine changes coupled with increases in serum metabolite makers indicative of improved gastrointestinal (GI) health (6,10).…”
mentioning
confidence: 99%
“…Transgenic goat milk containing human lysozyme could protect from mastitis in vitro and showed benefits in animal health for goats drinking the transgenic milk (Maga et al, 2006b;Maga et al, 2006a). Similarly, pigs (Tong et al, 2010) and cattle (Yang et al, 2011) expressing lysozyme in the mammary gland have been created.…”
Section: G Food Safetymentioning
confidence: 99%
“…Although lysozyme had no direct antibacterial activity against the tested bacteria in breast milk, this does not exclude an antibacterial effect on other bacteria, for example, gram-positive bacteria. In addition, breast milk lysozyme may modulate the gut microflora, either directly or after being processed by pepsin in the stomach into various antibacterial peptides (8,21,28).…”
Section: Vol 74 2008 Bacterial Survival In Lysozyme-rich Fluids Duementioning
confidence: 99%